Antibacterial silver and gold complexes of imidazole and 1, 2, 4-triazole derived N-heterocyclic carbenes. Issue 32 (25th July 2022) - Mather, Joel C.; Wyllie, Jessica A.; Hamilton, Alex; Soares da Costa, Tatiana P.; Barnard, Peter J.
Abstract : A series of gold(i ) and silver(i ) complexes of 1, 2, 4-triazolylidene and imidazolylidene based N-heterocyclic carbene ligands were prepared that show excellent antibacterial activity against clinically relevant bacterial pathogens. Abstract : A series of gold(i ) (4a–4h, 5a–5b ) and silver(i ) (3a–3h ) complexes of 1, 2, 4-triazolylidene and imidazolylidene based N-heterocyclic carbene ligands were prepared and the antibacterial activities of these complexes have been evaluated. The complexes were characterised using 1 H-NMR, 13 C-NMR, HRMS and in the cases of 3a, 3c, 4b and 5b by X-ray crystallography. The gold(i ) complexes with phenyl substituents (4a–4d ) were found to have potent antibacterial activity against Gram-positive bacteria, with the complexes of the 1, 2, 4-triazolylidene ligands being more active (4c, MIC = 4–8 μg mL −1 against Enterococcus faecium and 2 μg mL −1 against Staphylococcus aureus ) than the analogous imidazolylidene complexes 4a and 4b (4a, MIC = 64 μg mL −1 against E. faecium and 2–4 μg mL −1 against S. aureus ). Two of the silver(i ) complexes have promising antibacterial activity against Acinetobacter baumannii (3f, MIC = 2–4 μg mL −1 and 3g, MIC = 2 μg mL −1 ). Silver(i ) complex 3f and gold(i ) complex 4c were tested against multi-drug resistant bacterial strains and high levels of antibacterial activity were observed. The potential for antibacterial resistance to develop against these metal containing complexes was investigated and significantly, no resistance was observed upon continuous treatment, whilst resistance was developed against the widely used broad-spectrum antibiotic ciprofloxacin in the same bacterial strains, under the conditions tested. The solution and gas phase stabilities of the complexes have been investigated using a combination of 1 H-NMR, HRMS and detailed computational mechanistic studies were undertaken to gain insights into the possible decomposition reactions for silver complexes in aqueous solution.